Estudio de prefactibilidad para la instalación de una planta productora de chocolate en forma de chupetes endulzados con Stevia y rellenos de Aguaymanto (Physalis Peruviana L) elaborado con cacao orgánico (Theobroma Cacao L) proveniente de Junín - Marquez Vilela, Diego Gonzalo (2022)
The project seeks to determine the technical and economic-financial feasibility for the implementation of a chocolate production plant in the form of lollipops sweetened with stevia and filled with aguaymanto made with organic cocoa from Junín. The project will have a useful life of 5 years and will start activities in May 2021. The product will weigh 32,25g and will be intended for people between 6 and 55 years old in need of an organic and healthy product for consumption. The price for the market is S/. 1,5 and it is expected to satisfy a demand that, for the first year of the project, stands at 10 366 436 chocolates in the form of pacifiers and for the last period of 13 608 576 of the product, which will generate a sales income of S /. 15 549 654 and S/. 20 412 864 respectively. About the market study, a survey of 11 questions was carried out, a tool applied to three hundred and ninety-three (393) people, of which 71,50%, showed their willingness to buy the product. The location study gave as the location of the company the department of Lima and specifically the district of Chorrillos. The financing structure corresponds to 60% (S/. 984 757.80) for share capital and 40% (S/. 656 505,20) for bank loan, which totals an initial investment of S/. 1 641 263,01. The financial statements showed positive results for each of the life periods of the project, the economic and financial indicators such as the NPV are positive (VANE = S /. 12 563 405,99 and VANF = S /. 14 154 538,64), on the other hand the TIRE obtained is higher than the discount rate COK (TIRE = 184%) ¿ COK (10,05%) and the TIRF (323,80%) ¿ COK (10,05%), the recovery periods are 1 year and 10 months respectively, indicating that the project is viable.